Topographical anatomy and oncologic colon surgery: new or well forgotten old? - I. L. Chernikovskiy; N. V. Savanovich; A. A. Smirnov; A. V. Gavrilyukov; O. V. Oganesyan (Тазовая хирургия и онкология, 2017)
The article is devoted to the surgery standards for colorectal cancer, specific features of colon mobilization in patients with locally advanced colon cancer and the use of germ cell layers as anatomical landmarks. We describe the features and the volume of lymph node dissection during surgeries for left and right colon, the level of central vessels ligation during intervention and the criteria for assessing the quality of mesocolic excision. We studied the impact of these factors on overall and relapse-free survival, highlighted some aspects of mobilization of the right and left colon. The objective of this article was to contribute to the development of methodological guidelines for colon cancer surgery in compliance with the principles of complete mesocolic excision with central vessels ligation.